Impact of Immigration on HIV-1 molecular epidemiology in West Africa, Maghreb and Southern Europe. - (:unkn) unknown (My University, 2014)
There is global concern about the relation between international migration and the course of the AIDS epidemic. Maghreb is a North African region, which lies between sub-Saharan Africa and Europe. It has been turned recently into a region of immigration, since there are more and more flows of West African migrants hoping to reach European countries. Here we provide an overview on HIV-1 molecular epidemiology particularly in West African countries, Maghreb (Morocco, Algeria, Tunisia) and southern European countries (Spain, France, and Italy). The studies conducted in several countries of the region revealed different features of HIV-1 molecular epidemiology, especially for the distribution of viral subtypes and for transmitted drug resistance profiles. Furthermore, migration from West Africa to Europe seems to be a potential source of non-B subtype mobility to Maghreb and eventually to southern Europe, where HIV-1 non-B variants significantly increased in the last 10 to 15 years. As genetic differences between subtypes might impact the drug resistance pathways, it is important to provide continuous surveillance programs for the early detection of new variants spreading in the population before they become more prevalent, and to identify resistance profiles in different infected populations, especially migrants.
Keywords: African Research